2009
DOI: 10.1016/j.ejcts.2008.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the single or double chest tube applications after pulmonary lobectomies☆

Abstract: Insertion of two chest tubes is not more effective than the insertion of a single chest tube after pulmonary lobectomy. Moreover, using a single tube is in fact more effective than using two tubes in that it causes less postoperative pain and less pleural fluid loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 8 publications
(7 reference statements)
4
70
0
5
Order By: Relevance
“…The results of the randomized trials revealed that proper extension of the residual lung could be achieved even with one chest tube. These reports also revealed that there were no significant differences in the postoperative complications, whereas the overall costs were clearly reduced (Gomez-Caro et al 2006;Pawelczyk et al 2007;Okur et al 2009). However, most of the patients in these trials underwent pulmonary lobectomy using standard thoracotomy, therefore, these results cannot be fully applied to the patients treated by VATS, which is becoming mainstream for pulmonary surgery, especially in Japan (Ueda et al 2008;Kuwano et al 2012).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The results of the randomized trials revealed that proper extension of the residual lung could be achieved even with one chest tube. These reports also revealed that there were no significant differences in the postoperative complications, whereas the overall costs were clearly reduced (Gomez-Caro et al 2006;Pawelczyk et al 2007;Okur et al 2009). However, most of the patients in these trials underwent pulmonary lobectomy using standard thoracotomy, therefore, these results cannot be fully applied to the patients treated by VATS, which is becoming mainstream for pulmonary surgery, especially in Japan (Ueda et al 2008;Kuwano et al 2012).…”
Section: Discussionmentioning
confidence: 70%
“…There were no significant differences in the number of cases requiring thoracentesis (0 in both groups), the amount/duration of drainage or the maximum pain score between the two groups, which meant that PD1 was not inferior to PD2. Therefore, due to the lack of inferiority, and the advantages in saving cost and time to place and remove the second chest tube as well as in decreasing the risk of transcutaneous infection, PD1 should therefore be amount of drainage were reported to decrease in the patients treated with PD1 in one study (Okur et al 2009), but there were no statistically significant differences between PD1 and PD2 in two other reports (Gomez-Caro et al 2006;Pawelczyk et al 2007). The duration of drainage was shorter with PD1 in one report (different from the above report with a smaller amount of drainage with PD1) (Pawelczyk et al 2007), but the remaining reports revealed no significant differences between the groups (Gomez-Caro et al 2006;Okur et al 2009).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Despite the significant reducement of PP and requirement of analgesia ensured with the protection of intercostal nerve by the convenient methods during the opening and closure of thorax were showen in prospective randomised studies [10], the choice of pericostal sutures inducing PP can be interrogated. The extension of operation time due to the procedures for the protection of intercostal nerve can be a probable reason for this choice.…”
Section: Discussıonmentioning
confidence: 99%